Effects of methylmercury on male reproductive functions in Wistar rats - Fossato da Silva, Daniela A. [UNESP]; Teixeira, Carla T. [UNESP]; Scarano, Wellerson R. [UNESP]; Favareto, Ana Paula A.; Fernandez, Carla D. B.; Grotto, Denise; Barbosa, Fernando; Kempinas, Wilma de G. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
In this study we investigated the effects of subacute exposure to methylmercury (MeHg) on male reproductive functions in rats by means of determination of alterations in structural and functional parameters. Adult male Wistar rats received 0, 0.5, 1.0 or 3.0 mg/kg/body weight/day orally, daily MeHg for 14 days. Sperm motility, the relative sperm count and transit time in the caput/corpus epididymis, were all reduced at all doses. The lowest dose increased the number of sperm head abnormalities; daily sperm production was elevated at the intermediate dose; while at the highest dose there was a decrease in serum testosterone levels and a rise in mercury (Hg) content in reproductive organs, liver and kidneys. In conclusion, MeHg exposure produced damages on male reproductive functions which may be attributed, at least in part, to the reduction in serum testosterone levels. These consequences could potentially result in infertility in rats. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Reproductive toxicity; Methylmercury; Rat; Testosterone; Sperm; Testis; Epididymis; ICP-MS